2019
DOI: 10.3904/kjm.2019.94.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant, Gram-Negative Bacteria in Hospitalized Elderly Patients from Non-Hospital Long-Term Care Facilities

Abstract: Background/Aims: We investigated the risk of multidrug-resistant, gram-negative bacteria (MDRGNB) in hospitalized elderly patients from non-hospital long-term care facilities (LTCFs) and the antibiotic prescription pattern. Methods: All clinical cultures obtained within 48 hours of hospitalization from elderly patients of at least 55 years of age arriving at a 623-bed, public teaching hospital in Seoul, Republic of Korea from LTCFs between April 1, 2011 and April 1, 2012 were collected retrospectively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Studies carried out at ACHs also found that patients admitted from LTCFs had higher odds of colonization [14]. Exposure to antibiotics was found to be a risk factor for colonization of VRE in the rectum [18], and previous colonization of multidrug-resistant Gram-negative bacteria was the single risk factor [19] among patients transferred from LTCFs. Interestingly, a stay in an LTCF for longer than one year was revealed to be a protective factor for the carriage of VRE (subgroup 1, Supplementary Table 1), since residency in long-term care facilities may provide an opportunity for the person to person transmission of microorganisms.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies carried out at ACHs also found that patients admitted from LTCFs had higher odds of colonization [14]. Exposure to antibiotics was found to be a risk factor for colonization of VRE in the rectum [18], and previous colonization of multidrug-resistant Gram-negative bacteria was the single risk factor [19] among patients transferred from LTCFs. Interestingly, a stay in an LTCF for longer than one year was revealed to be a protective factor for the carriage of VRE (subgroup 1, Supplementary Table 1), since residency in long-term care facilities may provide an opportunity for the person to person transmission of microorganisms.…”
Section: Discussionmentioning
confidence: 89%
“…Studies carried out at ACHs also found that patients admitted from LTCFs had higher odds of colonization [ 14 ]. Exposure to antibiotics was found to be a risk factor for colonization of VRE in the rectum [ 18 ], and previous colonization of multidrug-resistant Gram-negative bacteria was the single risk factor [ 19 ] among patients transferred from LTCFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For grampositive organisms, the antimicrobial susceptibility test profile included penicillin (10U), ampicillin (10 μg), gentamicin (10 μg), teicoplanin (30 μg), vancomycin, ciprofloxacin (5 μg), clindamycin (2 μg), erythromycin (15 μg), and tetracycline (30 μg). The organism was classified as multidrug-resistant if it was resistant to the three major classes of antimicrobials (10). The organism was classified as pandrug-resistant when it was resistant to all classes of antimicrobial drugs except colistin.…”
Section: Methodsmentioning
confidence: 99%